Antifungal prophylaxis with liposomal amphotericin B and caspofungin in high-risk patients after liver transplantation: impact on fungal infections and immune system. Issue 2 (1st February 2016) - Perrella, A.; Esposito, C.; Amato, G.; Perrella, O.; Migliaccio, C.; Pisaniello, D.; Calise, F.; Cuomo, O.; Santaniello, W.
Abstract: Antifungal prophylaxis may be required in high-risk patients undergoing liver transplantation and for that reason we aimed to verify its role and its related impact on the graft. From January 2006 throughout 2012, 250 liver transplants were evaluated and 54 patients identified as being at higher risk were randomly selected to undergo the following schedule: 28 patients received liposomal amphotericin B and 26 received caspofungin. We evaluated, throughout 12 months, renal and liver function tests, bacterial and fungal infection episodes, and intensive care unit (ICU) stay, as well as the Th1 and Th2 cytokine network. Differences were analyzed according to non-parametric tests (two-tailed p values). Neither of the groups showed episodes of invasive fungal infection during the 12 months follow-up; however, patients receiving prophylaxis with liposomal amphotericin B had reduced episodes of bacterial infections coupled with an improved immune system response compared with those receiving caspofungin. Finally, a reduced stay in the ICU was also observed. In conclusion, even if the results of liposomal amphotericin B and caspofungin prophylaxis strategies did not differ in terms of invasive fungal infection rate, patients receiving prophylaxis with liposomal amphotericin B had a reduced ICU stay and an improved Th2 status, as well as a reduced number of post-transplant bacterial infections. Further studies are required to better address and evaluate these findings.